Polycythaemia Vera Results of Repeated Radioisotope Studies in 53 Patients During a Five-Year Period - Varela, J. E.; Rochna Viola, E. M.; Carmena, A. O.; Etcheverry, M. A.; Kremenchuzky, S. (Nuklearmedizin - NuclearMedicine, 1963)
53 patients with a confirmed diagnosis of polycythaemia vera have been studied by means of radioisotope techniques before and after P32 therapy for a five-year period.Results of measurements of the plasma iron pool, the Fe59 plasma half-life, plasma iron turnover, Fe59 incorporation and red cell survival are reported. Various indices were used to compare individuals of different sex and weight and to compare untreated patients, patients in remission after therapy and in relapse. These are discussed in detail.It is demonstrated that the routine haematological tests alone do not provide sufficient information to arrive at a correct diagnosis of the haematological status of an individual patient.53 malades souffrants d’une polycythemic varie ont été examines pendant 5 ans avant et après une thérapie au P32 par la méthode aux isotopes.On rapporte les résultats de la mesure du pool du Fe59 plasmique, de la demivie de la fixation du Fe59 et de la demivie des globules rouges. Des indices différents sont adoptés pour permettre la comparaison entre des malades de différent age et sexe état de rémission et en réchute.Les résultats sont discutés en détail. Il est prouvé que les examens hématologiques de routine ne sont pas suffisants pour établir le diagnostic correct de l’état hématologique d’un malade.53 Patienten mit gesicherter Polycythaemia vera wurden vor und nach P32-Therapie innerhalb eines Zeitraumes von 5 Jahren mit Hilfe von Radioisotopenmethoden untersucht.Die Ergebnisse der Messungen des Plasmaeisenpools, der Fe59-Halbwertszeit im Plasma, des Plasmaeisenumsatzes, des Fe59-Einbaus und der Lebensdauer der Erythrozyten werden berichtet. Verschiedene Indizes werden verwendet, um Patienten verschiedenen Geschlechts und Gewichts und unbehandelte Patienten, solche in Remission und solche im Rückfall miteinander vergleichen zu können. Diese Ergebnisse werden im einzelnen diskutiert.Es wird nachgewiesen, daß die routine-hämatologischen Untersuchungen allein nicht ausreichen, um zu einer korrekten Diagnose des hämatologischen Zustands des individuellen Patienten zu gelangen.